Carex longicolla (Cyperaceae), a new sedge from China - Deng, Yunfei (Phytotaxa, 2014)
Carex longicolla is described as a new species in section Lageniformes from South China. It is similar to C. truncatigluma, but differs from the latter in its culms more short, 5–10 cm long, spikelets 3–5, close each other, neck equal to or longer than nutlet, 1.5–2 mm long.